Trinidad and tobago : The Energy Boom and Proposals for a Sustainable Fiscal Policy. (IMF Working Papers; Working Paper ;, 2005)
Trinidad and Tobago is experiencing an energy boom stronger than the ones in 1970s and 1980s. The main fiscal policy challenge is to ensure that the increased revenues from the ultimately exhaustible resources are used in a way that protects the competitiveness of the nonenergy sector, builds assets to ensure intergenerational equity, and provides a cushion for stabilization. This paper derives estimates of a sustainable level of primary fiscal balance using Friedman's permanent income hypothesis. These estimates can be used as a guide for the formulation of medium- and long-term fiscal policy frameworks.